2020
DOI: 10.1530/eje-20-0377
|View full text |Cite
|
Sign up to set email alerts
|

ENDOCRINOLOGY IN THE TIME OF COVID-19: Remodelling diabetes services and emerging innovation

Abstract: The COVID-19 pandemic is a major international emergency leading to unprecedented medical, economic and societal challenges. Countries around the globe are facing challenges with diabetes care and are similarly adapting care delivery, with local cultural nuances. People with diabetes suffer disproportionately from acute COVID-19 with higher rates of serious complications and death. In-patient services need specialist support to appropriately manage glycaemia in people with known and undiagnosed diabet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
1
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 19 publications
0
70
1
3
Order By: Relevance
“…Telemedicine was one of the key strategies to enable individuals to continue receiving medical attention while staying safe at home [16,38,44,47,48,49,50]. The lack of other options or the identification of telemedicine's potential led to its quick legal approval and reimbursement in several countries [33,45,46,49,51,52]. A variety of digital components were adopted in different places for diabetes care during the pandemic [41,53,54].…”
Section: Transitioning From In-person To Telemedicine Carementioning
confidence: 99%
See 3 more Smart Citations
“…Telemedicine was one of the key strategies to enable individuals to continue receiving medical attention while staying safe at home [16,38,44,47,48,49,50]. The lack of other options or the identification of telemedicine's potential led to its quick legal approval and reimbursement in several countries [33,45,46,49,51,52]. A variety of digital components were adopted in different places for diabetes care during the pandemic [41,53,54].…”
Section: Transitioning From In-person To Telemedicine Carementioning
confidence: 99%
“…In Australia webchats, podcasts and a guide were developed [42]. The United Kingdom wisely developed a consensus document for treating PwD with COVID-19 and another for outpatients' appointment prioritization [49]. A guide for HCPs was also published in Bangladesh [70].…”
Section: Development and Adaptation Of Resources And Channelsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, these changes are being implemented without clear plans or directives for managing other comorbidities often associated with diabetes, such as hypertension and established cardiovascular disease (CVD). There has also been a push toward more patient self-managed care via online structured educational resources, 13 yet the reach of such programs is not known. Prior to the COVID-19 pandemic, a meta-analysis including randomized controlled trials (RCTs) that compared telemedicine interventions with usual care found that systems allowing for medication adjustments with or without text messaging or a web portal improved glycated hemoglobin A1c (HbA1C) but not other clinically relevant outcomes in patients with diabetes.…”
Section: Introductionmentioning
confidence: 99%